Association of Right Ventricular Myocardial Blood Flow With Pulmonary Pressures and Outcome in Cardiac Amyloidosis - Harms, Hendrik J.; Clemmensen, Tor; Rosengren, Sara; Tolbod, Lars; Pilebro, Björn; Wikström, Gerhard; Granstam, Sven-Olof; Kero, Tanja; Di Carli, Marcelo; Poulsen, Steen Hvitfeldt; Sorensen, Jens (JACC. Cardiovascular imaging, 2023)
Cardiac amyloidosis (CA) is a restrictive and infiltrative cardiomyopathy, characterized by increased biventricular filling pressures and low output. Symptoms are predominantly of right heart origin. The role of right ventricular (RV) myocardial blood flow (MBF) in CA has not been studied. This study aimed to first associate RV MBF measured by using positron emission tomography (PET) with reference standards of RV pressures and then to explore its prognostic value in CA. Cardiac PET was performed at rest in 52 patients with CA and 9 healthy control subjects. MBF was quantified from the right and left ventricles by using 11C-acetate, 15O-water, or both (n = 25). RV pressure was measured invasively or by echocardiography. Associations between biventricular MBF toward symptoms, RV function, and outcome (death or acute heart failure) were studied in patients with CA. MBF of the right ventricle (MBFRV) and the ratio of MBFRV and MBF of the left ventricle (MBFRV/LV) for the 2 tracers were significantly correlated (r > 0.92). MBFRV was directly correlated with RV systolic pressures with both tracers (P ≤ 0.005). MBFLV was inversely correlated with wall thickness (P < 0.0001). MBFRV/LV was significantly associated with N-terminal pro–B-type natriuretic peptide levels, NYHA functional class, RV pressures, and RV systolic function (all; P < 0.001). Twenty-six cardiac events (25 deaths) occurred during follow-up (median 44 months). MBFRV/LV higher than 56% was associated with a diagnosis of pulmonary hypertension (AUC: 0.96 [95% CI: 0.91-1.00]; P < 0.0001); and predicted outcome with HR: 9.0 (95% CI: 4.2-14.5), P < 0.0001). Measurements of MBFRV using PET are feasible, as confirmed with 2 different tracers. Imbalance between RV and LV myocardial perfusion is associated with increased RV load and adverse events in cardiac amyloidosis. [Display omitted]